PENERAPAN METODE REWARD DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VII DI M TSN 7 AGAM - Adria Nelisa Putri; Hidra Ariza; Murni HS (KOLONI, 2023)
This research discusses how to apply rewards to increase Aqidah Akhlak motivation at MTsN 7 Agam. The type of research used is a qualitative research method by exploring data in the field related to problems that have been formulated using descriptive analysis methods to provide an overview of the application of the reward method in increasing student learning motivation in the Aqidah Ahalak class VII subject at MTSN 7 Agam. The data in this research was obtained through primary and secondary data, namely direct observation and interviews with Aqidah Akhlak teachers at the research location and also direct interviews with students at MTsN 7Agam using research instruments in the form of observation guidelines, interview guidelines, documentation and analyzed using data reduction steps, presentation of data and conclusions. This research aims to determine the application of rewards at MTsN 7 Agam, to determine the forms of application of rewards at MTsN 7 Agam, and to determine the application of rewards to increase student motivation at MTsN 7 Agam. Research Results: The process of applying rewards to increase student motivation at MTsN 7 Agam, namely that teachers and students make an agreement that if students work well and excel, then their achievements will be rewarded. There are forms of imbalance given to students such as giving gifts, praise, body movements such as applause, thumbs up, etc.